Hunting, swimming, and worshiping: human cultural practices illuminate the blood meal sources of cave dwelling Chagas vectors (Triatoma dimidiata) in Guatemala and Belize. - Lori Stevens; M Carlota Monroy; Antonieta Guadalupe Rodas; Patricia L Dorn (Public Library of Science (PLoS), 2014)
Triatoma dimidiata, currently the major Central American vector of Trypanosoma cruzi, the parasite that causes Chagas disease, inhabits caves throughout the region. This research investigates the possibility that cave dwelling T. dimidiata might transmit the parasite to humans and links the blood meal sources of cave vectors to cultural practices that differ among locations.We determined the blood meal sources of twenty-four T. dimidiata collected from two locations in Guatemala and one in Belize where human interactions with the caves differ. Blood meal sources were determined by cloning and sequencing PCR products amplified from DNA extracted from the vector abdomen using primers specific for the vertebrate 12S mitochondrial gene. The blood meal sources were inferred by ≥ 99% identity with published sequences. We found 70% of cave-collected T. dimidiata positive for human DNA. The vectors had fed on 10 additional vertebrates with a variety of relationships to humans, including companion animal (dog), food animals (pig, sheep/goat), wild animals (duck, two bat, two opossum species) and commensal animals (mouse, rat). Vectors from all locations fed on humans and commensal animals. The blood meal sources differ among locations, as well as the likelihood of feeding on dog and food animals. Vectors from one location were tested for T. cruzi infection, and 30% (3/10) tested positive, including two positive for human blood meals.Cave dwelling Chagas disease vectors feed on humans and commensal animals as well as dog, food animals and wild animals. Blood meal sources were related to human uses of the caves. We caution that just as T. dimidiata in caves may pose an epidemiological risk, there may be other situations where risk is thought to be minimal, but is not.